Binding of brush border myosin I to phospholipid vesicles (The Rockefeller University Press, 1990)
The actin filament core within each microvillus of the intestinal epithelial cell is attached laterally to the plasma membrane by brush border (BB) myosin I, a protein-calmodulin complex belonging to the myosin I class of actin-based mechanoenzymes. In this report, the binding of BB myosin I to pure phospholipid vesicles was examined and characterized. BB myosin I demonstrated saturable binding to liposomes composed of anionic phospholipids, but did not associate with liposomes composed of only neutral phospholipids. The binding of BB myosin I to phosphatidylserine and phosphatidylglycerol vesicles reached saturation at 4-5 x 10(-3) nmol protein/nmol phospholipid, while the apparent dissociation constant was determined to be 1-3 x 10(-7) M. Similar to the free protein, membrane-associated BB myosin I bound F-actin in an ATP-sensitive manner and demonstrated actin-activated Mg-ATPase activity. Immunoblot analysis of peptides generated from controlled proteolysis of vesicle-bound BB myosin I provided structural information concerning the site responsible for the membrane interaction. Immunoblot staining with domain-specific mAbs revealed a series of COOH-terminal, liposome-associated peptides that were protected from digestion, suggesting that the membrane-binding domain is within the carboxy-terminal "tail" of the BB myosin I heavy chain.